Pendekatan Sintesis Narasi Sabat Tanah dan Tradisi Ma’pebulam serta Implementasinya Bagi Penanganan Krisis Ekologi Tanah dan Air - Sucipto, Jimmy (Institut Agama Kristen Negeri Toraja, 2024)
From this research, it was found that ecological crises, especially soil and water, can be prevented by providing space for soil and water to